JOURNALISTIC ETHICS AND SECONDARY VICTIMIZATION IN THE PRINT MEDIA IN SERBIA - Božović, Dragana T (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
Publishing of information which cause violation of the victims’ rights to dignity, privacy and safety is a very common non-professional practice of journalists reporting on crime. This creates conditions for the secondary victimization which manifests itself through the aggravation of the negative consequences caused by criminal act. The aim of this paper is to examine how print media in Serbia provoke secondary victimization through the violation of ethical principles in reporting about victims of criminal acts. Content analysis is used to analyse news articles about victims of domestic violence published in the period from January 1st to June 30th 2016. Rotary sample included three printed editions of newspapers with different editorial policies and national coverage: quality daily newspaper Politika, middle-market tabloid Blic and tabloid newspaper Kurir. In order to understand the application of the ethical code of journalism in reporting on domestic violence, the research also includes interviews with some of the members of the Press Council. The results show that there are differences between the analyzed newspapers in the approach to the topic of domestic violence and reporting on the victims of this type of crime. In the analyzed period Blic made the highest number of ethical violations, followed by the newspaper Kurir, while in Politika there is significantly fewer articles that create the conditions for secondary victimization. Revealing the identity of the victims, unjustified search for the reasons for the occurrence of violence and publishing other data that are not directly related to informativeness of the text, but intrude into the private domain, are some of the most common violations of journalists’ ethical code.